“PEMBANGKANGAN” KEPALA DAERAH KEPADA MENTERI DI INDONESIA PADA ERA OTONOMI DAERAH - Mahmuzar Mahmuzar (Jurnal EL-RIYASAH, 2022)
The relationship between the local and central governments in the era of regional autonomy should be harmonious because the local government is a subsystem of the national government's that final responsibility lies with the President. In addition, one of the objectives of regional autonomy is to create harmonious relations between the central and local governments. But in fact, there are several regional heads in the Unitary State of the Republic of Indonesia which carried out "defiance" to state minister. The regional head who conducts "insubordination" to the state minister in the Unitary State of the Republic of Indonesia, cannot be dismissed from his position as regional head because Act Number 23 of 2014 concerning Regional Government does not explicitly regulate it as one the reasons regional heads can dismiss from his position, except that disobedience is carried out by the regional head in order not to carry out a national strategic program launched by the central government through non-departmental ministries/agencies.